Assessing the Effectiveness of Evidence-Based Medicine in Practice: A Case Study of First-Time Anterior Shoulder Dislocations. (16th January 2019) - Hutyra, Carolyn A.; Streufert, Benjamin; Politzer, Cary S.; Agaba, Perez; Rubin, Elka; Orlando, Lori A.; Taylor, Dean C.; Mather, Richard C.
Abstract : Background: The dissemination of evidence-based information into medical practice is essential to provide patients with optimal care and realize society's substantial investments in medical research. Effective information delivery and treatment utilization may lead to improvements in patient outcome, reductions in cost, and an overall lower burden on the health-care system. This study examines the dissemination of medical evidence following a first-time anterior shoulder dislocation (FTASD) and assesses the impact of potential dissemination strategies. Methods: The state of evidence dissemination into clinical practice for FTASD was evaluated with use of the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. The treatment pathway for patients with FTASDs was mapped and evaluated using data that were collected through an orthopaedic shoulder-specialist survey and with review of a claims database. Results: A total of 1, 755 patients with an FTASD were identified through a national claims database; 50% of patients followed up with a care provider within 30 days after an emergency department (ED) or urgent care visit. Based on shoulder-specialist survey data, physician estimates of the risk of redislocation within a 2-year window aligned with medical evidence 59% of the time. Only 29% of patients obtained information for FTASD that aligns with high-level medical evidence. Conclusions: There are gaps and deficiencies in the dissemination and application of evidence in the treatment of FTASDs. Specifically, patients have limited exposure to health-care encounters where appropriate information related to low rates of follow-up following ED or urgent care visits may be communicated. Evaluating the current state of practice and identifying areas of improvement for the dissemination of evidence regarding FTASDs can be achieved through application of the RE-AIM framework. Greater consideration and resourcing of dissemination and implementation strategies may improve the dissemination and the impact of existing medical evidence.